1998
DOI: 10.1093/geronb/53b.2.p130
|View full text |Cite
|
Sign up to set email alerts
|

Attention and Driving Performance in Alzheimer's Disease

Abstract: The present study examined the relationship between visual attention measures and driving performance in healthy older adults and individuals with very mild and mild dementia of the Alzheimer type (DAT). Subjects were administered an on-road driving assessment and three visual attention tasks (visual search, visual monitoring, and useful field of view). The results indicated that error rate and reaction time during visual search were the best predictors of driving performance. Furthermore, visual search perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
0
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(122 citation statements)
references
References 31 publications
8
110
0
4
Order By: Relevance
“…52 Compared to other visual and cognitive tools, there is a poor correlation using the UFOV with driving ability to predict collision rates. [53][54][55] …”
Section: Methods Of Assessmentmentioning
confidence: 99%
“…52 Compared to other visual and cognitive tools, there is a poor correlation using the UFOV with driving ability to predict collision rates. [53][54][55] …”
Section: Methods Of Assessmentmentioning
confidence: 99%
“…The effect size yielded by combining these eight studies, d = 0.945, was well above Cohen's threshold for a large effect (d=0.8) even after the correction was applied. Additionally, the eight studies were subdivided into 3 categories: studies conducted by individuals with financial interests in the UFOV ® test Owsley et al, 1991;Roenker et al, 2003), studies in which data were collected and analyzed in independent laboratories that subsequently requested collaboration of UFOV ® creators during the preparation of manuscripts (Duchek et al, 1998;Myers et al, 2000;Rizzo et al, 1997) and studies in which the data were collected, analyzed, and reported independently (Wood & Troutbeck, 1995;Cushman, 1996). The mean effect sizes for these three subgroups (Cohen's d ) were 0.831, 1.133, and 1.109, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Además de estos datos, también se ha observado que los pacientes presentan manifestaciones clínicas que se han vinculado a problemas relacionados con el CE desde los primeros momentos de la EA, como son las dificultades para realizar AVD, para conducir o alteraciones en la comprensión del lenguaje (Duchek et al, 1998;Perry y Hodges, 1999;Faust, Balota, Duchek, Gernsbacher y Smith, 1997). A continuación analizaremos detalladamente la evidencia neuropsicológica con respecto a las operaciones de CE en los inicios de la EA.…”
Section: El Control Ejecutivo En La Eaunclassified
“…Del mismo modo, el análisis del funcionamiento ejecutivo en la enfermedad de Alzheimer (EA) ha sido objeto de un gran interés. Diversos estudios muestran que estos sujetos tienen dificultades a la hora de llevar a cabo actividades de la vida diaria (AVD) que demandan al CE, y muestran alteraciones neuropsicológicas relacionadas con el mismo desde estadios relativamente tempranos de la enfermedad (Alberoni, Baddeley, Della Sala, Logie y Spinnler, 1992;Amieva, Phillip, Della Sala y Henry, 2004;Belleville, Rouleau y Van der Linden, 2003;Duchek, Hunt, Ball, Buckles y Morris, 1998;Martini, Benke, Domahs y Delazer, 2003;Perry y Hodges, 1999). Además, recientes investigaciones neuropatológicas, electrofisiológicas y de neuroimagen han mostrado que, además de otras áreas más posteriores y subcorticales, se encuentran afectadas áreas anteriores como el córtex prefrontal, que están implicadas en las manifestaciones clínicas de la EA desde etapas muy iniciales (Azari et al, 1992; Berendse, Verbundt, Scheltens, van Dijk y Jonkman, 2000; Delbeuck, Collette y Van der Linden, 2007;Horwitz, Grady, Sclageter, Duara y Rapoport, 1987;Grady, Furey, Pietrini, Horwitz y Rapoport, 2001;Wang et al, 2007).…”
Section: Introductionunclassified